2016
DOI: 10.1016/j.ijheatmasstransfer.2016.03.077
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of nitrogen gas in a liquid helium cooled vacuum tube following sudden vacuum loss – Part II: Analysis of the propagation speed

Abstract: The propagation of near-atmospheric nitrogen gas entering a liquid helium (LHe) cooled vacuum tube following an accidental loss of vacuum will be strongly influenced by condensation of the gas on the tube wall. Our previous experimental study revealed that in presence of condensation, the propagation speed of the gas front decreases nearly exponentially as the front advances in the tube. In the present paper the exponential decrease is studied analytically. We reduce the analytical model of the front speed, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The sensitivities agree very well with those documented in [2]. These encapsulates were then used in a series of experiments [6,7] (column B of Table 1), which involved several thermal cycles between 295 K and 4.2 K. After these experiments, we performed systematic tests to study the shift in calibration due to potting. Columns from C to F of Table 1 show the chronology of these thermal tests.…”
Section: Effect Of Potting On the Thermometer Performance A) Testing Proceduressupporting
confidence: 74%
“…The sensitivities agree very well with those documented in [2]. These encapsulates were then used in a series of experiments [6,7] (column B of Table 1), which involved several thermal cycles between 295 K and 4.2 K. After these experiments, we performed systematic tests to study the shift in calibration due to potting. Columns from C to F of Table 1 show the chronology of these thermal tests.…”
Section: Effect Of Potting On the Thermometer Performance A) Testing Proceduressupporting
confidence: 74%
“…In order to better understand the complex coupled heat and mass transfer processes involved in a beamline vacuum break event, pioneering work has been carried out in our cryogenics lab by Dhuley and Van Sciver via venting room-temperature nitrogen (N 2 ) gas from a buffer tank to a LHe cooled vacuum tube [9,10]. Their experiments with normal liquid helium (He I) showed that the gas-front propagation slowed down nearly * Corresponding: wguo@magnet.fsu.edu exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…Their experiments with normal liquid helium (He I) showed that the gas-front propagation slowed down nearly * Corresponding: wguo@magnet.fsu.edu exponentially. This deceleration was attributed to gas condensation to the tube wall [10], but a quantitative analysis on how the condensation leads to the observed exponential slowing down was not provided. Another limitation in these early experiments is that the tube system was not suitable for measurements with the superfluid phase of liquid helium (He II).…”
Section: Introductionmentioning
confidence: 99%